Effects of information on intentionality attributions and judgments: Punishing negligence and praising the caring for information - Andreas Haupt; Tobias Uske (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
Understanding how observers attribute intentionality to people in the focus of their attention helps in shedding light on punishment behavior. In this paper we approach impartial observers' attributions of intentionality and the attachment of praise and blame to perpetrators of external effects. In line with findings of Joshua Knobe (Knobe, 2003, 2006), we argue that intentionality attributions to these perpetrators are more likely, if observers consider the externality as morally bad instead of good. Due to this asymmetry, people punish the perpetrators of negative externalities more severely than they reward those of positive ones. In this paper we extend this explanation of the praise-blame bias by arguing that not only moral considerations but also the information setting of perpetrators of externalities are taken into account by observers. To that end, we analyze the answers to vignettes of 240 undergraduate students of Friedrich Schiller University of Jena. We take advantage of ordinary least square, logistic, and multinomial-logistic regression models to predict increases in chances to attribute intentionality and to attach praise or blame. We show that the awareness of, and the caring for, information related to the side effects of actions crucially affect the judgments of impartial observers.
Keywords: C91; D03; D62; D63; D72; 330; intentionality; externalities; punishment; praise; moral bias